(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the era of globalization like any other economic sector, the higher education sector is also driven by intense global competition and this has become a major challenge for institutions to retain and engage competent faculty members. Thus, the purpose to this study is to examine the engagement levels of faculty members in Higher Education Institutions of Himachal Pradesh. The study adopts a cross-sectional survey design with a sample of 360 faculty members employed in Higher Education Institutions of India. Majority of the faculty members were often engaged, which shows they were engaged only once in a week while discharging their duty. While amongst the three dimensions of employee engagement, faculty members had high dedication levels followed by vigor and absorption. The study cites a major concern for Higher Education Institutions. Present study will help institutional academic bodies to bring reform in their HR Policy and to be focused on their institution specific factors that influence and contribute to restore the disengaged faculties